Pelatihan Pendampingan Akreditasi Jurnal Ilmiah pada Rumah Jurnal PTKIS Se-Karesidenan Madiun - Fathoni, Khoirul; Witasari, Rinesti (Civiliza Publishing, 2023)
This training activity aims to improve the standardization of the quality of management of scientific journals at PTKIS throughout the Madiun residency both in terms of management and substance electronically based on Arjuna's provisions. Participants in the training activity were editors of scientific journals at PTKIS throughout the Madiun residency which included (INSURI Ponorogo, IAI Ngawi, STAINU Madiun, STAI Madiun, IAI RM Ngabar, STAINU Pacitan, and STAI Al-Fattah Kikil Pacitan) with 40 journal editors participating. The activity was carried out in two sessions, namely the first session on the management of scientific journals and the second session on the substance of scientific journals, and continued with submitting the journal to Arjuna, for accreditation. Through the stages that have been passed, this training activity can provide a concrete picture related to the implementation of journal accreditation, as well as provide motivation to all editors of scientific journals in Madiun Residency PTKIS to continue to improve the quality of journals in each PTKIS managed through Arjuna accreditation. Thus, it is hoped that all scientific journals at PTKIS throughout the Madiun Residency can be re-accredited.